Susceptibility of perivenous macrophages to PRRSV-1 subtype 1 LV and PRRSV-1 subtype 3 Lena using a new vein explant model - Han, Shaojie; Oh, Dayoung; Xie, Jiexiong; Nauwynck, Hans J. (Frontiers in Cellular and Infection Microbiology, 2023)
Vessel pathology such as increased permeability and blue discoloration is frequently observed with highly pathogenic PRRSV strains. However, data concerning the viral replication in the environment of blood vessels are absent. In the present study, ex vivo models with swine ear and hind leg vein explants were established to study the interaction of PRRSV-1 subtype 1 reference strain LV and highly pathogenic subtype 3 strain Lena with perivenous macrophages. The replication characteristics of these two strains were compared in vein explants by immunofluorescence analysis. The explants maintained a good viability during 48 hours of in vitro culture. We found that CD163-positive macrophages were mainly present around the veins and their number gradually decreased with increasing distance from the veins and longer incubation time. More CD163+Sn- cells than CD163+Sn+ cells (6.6 times more) were observed in the vein explants. The Lena strain demonstrated a higher replication level than the LV strain, with approximately 1.4-fold more infected cells in the surrounding areas of the ear vein and 1.1-fold more infected cells in the leg vein explants at 48 hours post inoculation. In both LV and Lena inoculated vein explants, most infected cells were identified as CD163+Sn+ (> 94%). In this study, an ex vivo vein model was successfully established, and our findings will contribute to a better understanding of the vein pathology during viral infections (e.g., PRRS, classical and African swine fever).